"Битви народів": історія і сучасність самопозиціонування на тлі глобалізаційних процесів (міжнародна конференція 6-7 листопада 2017 p., Лейпциг, Німеччина) - Полторак, В. (Чорноморська минувшина, 2017)
6-7 листопада в саксонському місті Лейпцигу (Німеччина) відбулась міжнародна Міждисциплінарна конференція/симпозіум «Самопозиціонування східноєвропейських спільнот у глобальних відносинах - концепції простору та самопрезентації у шкільних підручниках» (Self-Positioning of Eastern European Societies in Global Relations – Conceptions of Space and Self-Presentations in School Textbooks), організована EEGA (The Leibniz ScienceCampus «Eastern Europe – Global Area»). В роботі симпозіуму взяли участь як доповідачі з України, так і українські дослідники, які проходять стажування та працюють в Німеччині. On November 6-7, the International Interdisciplinary Conference / Symposium "Self-Positioning of Eastern European Communities in Global Relations - Concepts of Space and Self-Presentation in School Textbooks" was organized by EEGA (The Leibniz ScienceCampus, Eastern Europe - Global Area), DGO (The German Association for East European Studies), GEI (Georg Eckert Institute for International Textbook Research) and GWZO (Herder Institute for Historical Research on East Central Europe, Leibniz Institute for the History and Culture of Eastern Europe in Leipzig, Germany. The symposium was attended by speakers from Ukraine, as well as Ukrainian scholars trained and working in Germany. 6-7 ноября EEGA (The Leibniz ScienceCampus, Восточная Европа - глобальный регион), DGO (Германская ассоциация восточноевропейских исследований), GEI (Институт международных исследований учебников им. Джорджа Эккера) и GWZO (Институт исторических исследований им. Гердера в Восточной Центральной Европе, Институт истории и культуры Восточной Европы им. Лейбница) организовали в Лейпциге Международную междисциплинарную конференцию / симпозиум «Самопозиционирование восточноевропейских сообществ в глобальных отношениях - концепции пространства и самопрезентация в школьных учебниках». В симпозиуме приняли участие исследователи из Украины, а также украинские ученые, обучающиеся и работающие в Германии.